Workability, fiber distribution, and mechanical properties of UHPC with hooked end steel macro-fibers. (10th November 2020) - Hung, Chung-Chan; Chen, Yueh-Ting; Yen, Cheng-Hao
Abstract: Ultra high-performance concrete (UHPC) has superior mechanical and durability performance, which has motivated researchers and engineers to extensively explore its applications in civil engineering. While straight steel micro-fibers are frequently adopted to reinforce UHPC in existing engineering applications, studies have reported that deformed steel macro-fibers outperform straight steel micro-fibers in terms of enhancing the post-peak response and ductility of UHPC, which is of critical importance in seismic resistant design and applications. However, there lingers a major concern regarding the workability of deformed steel macro-fiber reinforced UHPC. Therefore, a thorough investigation was performed in this study to address this issue. A series of tests were carried out to study the effect of silica sand and fiber contents on the performance of fresh UHPC, including restricted and non-restricted deformability, filling ability, horizontal and vertical velocities, passing ability, and fiber distribution. In addition to the workability, the influences of silica sand and fiber contents on the compressive and tensile behavior of UHPC with deformed steel macro-fibers at 28 and 90 days were investigated. The results indicated that although a higher silica sand content led to an improved workability for UHPC, it reduced the homogeneity of fiber distribution. Furthermore, the inclusion of a 1% volume fraction of deformed steel macro-fibers was found to improve the workability of UHPC but reduced the compressive strength, which was contrary to the effect of straight steel micro-fibers at the same volume fraction. Increasing the fiber content from 1% to 2% increased the plastic viscosity of UHPC, which improved the fiber distribution and alleviated the blocking effect of steel bars. The use of the standard slump flow test with the criteria suggested by ACI 237R was a feasible approach to evaluate the fiber distribution and passing ability of UHPC with hooked end steel macro-fibers. Overall, the UHPC reinforced with a 2% volume fraction of deformed steel macro-fibers had good workability and fiber distribution when its plastic viscosity was adequately controlled.